Liquid-liquid equilibrium for methyl butyl ketone + o-, m-, p-cresol + water ternary systems and COSMO-SAC predictions. (December 2018) - Zhou, Shaoming; Xiong, Kangning; Li, Libo; Chen, Yun
Highlights: LLE data for MBK-cresols-water ternary systems were measured from 333.2 K to 353.2 K. Excellent agreement between experimental data and predictions from NRTL and UNIQUAC. Ternary phase diagrams could be predicted by the COSMO-SAC model. Abstract: The liquid–liquid equilibrium (LLE) data for the three ternary systems, methyl butyl ketone (MBK) +  o -, m -, p -cresol + water, were measured at 333.2 K and 353.2 K under 101 kPa in this work. Distribution coefficient and selectivity for cresols were calculated from the experimental tie-line data to evaluate the performance of MBK extracting cresols from the aqueous solution. The experimental tie-line data were correlated by the NRTL and UNIQUAC activity coefficient models, and both models showed good agreement with the experimental data. The COSMO-SAC model (conductor-like screening model for segment activity coefficient) was employed to predict LLE phase diagrams for the studied systems with root mean square deviations less than 3%.